Can periodontitis affect the COVID-19 severity, symptoms, hospital stay, and mortality? A case–control study - Macherla, Shravya; Chopra, Aditi; Ramanarayanan, Venkitachalam; Das, Rajat Subra; Garg, Rupesh (Frontiers in Public Health, 2024)
Background/ purpose: Poor oral hygiene and periodontal disease have been identified as a potential risk factor for the Coronavirus virus disease of 2019 (COVID-19). The present study aims to determine the association between periodontitis and COVID-19 severity, nature of symptoms, mortality, and hospital stay.Methods: 163 COVID-19-positive patients (Males-93; Females-70) were divided into control (asymptomatic-mild symptoms; N= 120) and case (moderate-severe symptoms; N= 43). The severity of periodontal disease, Oral hygiene status (OHI), pocket depth (PD), bleeding on probing (BOP), number of decayed/ missing/ filled teeth, mortality, duration of stay in hospital, oxygen requirement, nature of COVID-19 symptoms were assessed in both the groups. Association between the severity of periodontitis and COVID-19 was done with age, gender, comorbidities, oral hygiene, and smoking status.Results: Periodontitis increases the severity of COVID-19 by 3.7 times (p=0.002). A statistically significant difference was noted for symptoms like dizziness (p=0.036), running nose/cold (p=0.009), and headache (p=0.005) in the presence of periodontitis. The risk estimation of death to live with periodontitis was 1.03. The mean duration of stay was higher in individuals with periodontitis compared to control.There is a positive association between periodontal disease and COVID-19. Periodontitis is a potential risk for COVID-19. It increases the severity of COVID-19 and alters the symptoms.Hence, periodontal disease management should be an integral part of managing patients with coronavirus infection.